Rancang Bangun Sistem Informasi Kepegawaian Berbasis Website Pada PT. XYZ - choji, ferdian; Fransen, Lisa Amelia; Hermawan, Hermawan (MDP Student Conference, 2024)
PT XYZ is a building materials manufacturing company that focuses on products made of mild steel raw materials in the form of roofs, floors, partitions and framing, which also has 60 employees divided into several divisions. At XYZ in processing HR data has been computerized, but in data management and staffing data storage it is still not optimal. Based on these problems, a staffing information system was created at PT The website-based XYZ was created with the aim of being able to assist companies in processing employee data effectively and efficiently and is expected to be able to minimize errors and data loss. The method used in making this system is the RUP (Rational Unified Process) method, while the system design uses the Visual Studio Code, MySQL, and Laravel applications as a framework with the PHP programming language. The final result obtained is that the company can manage employee data, absences, layoffs, punishment and rewards, assignments, permission/leave and recruitment.